Plumber's licensing study guide - Frankel, Michael. frey50; Woodson, R. Dodge 1955- (New York : McGraw-Hill Professional ; London : McGraw-Hill [distributor], 2013)
Featuring more than 400 practice questions and answers providing everything you need to prepare for and pass the Journeyman and Master Plumber's licensing exams on the first try. Practical up-to date resource filled with study tips, detailed illustrations, calculations,conversion tables, and troubleshooting points. Both metric and U.S. units are included, fully revised for the 2012. International Plumbing Code and 2012 Uniform Plumbing code.
Administrative policies and procedures -- Micellaneous policies -- Water supply and backflow prevention -- Water heaters, heat exchangers, and boilers -- Sanitary drainage -- Fixtures and faucets -- Indirect waste -- Vents -- Storm water drainage -- Traps, cleanouts, and special waste -- Interceptors and separators -- Medical and nonmedical gases -- Alternative engineered and special systems -- Gray-water recycling systems -- Natural gas -- Guide to taking the test.
Previous ed.: 2007.
Keywords: Plumbing; Plumbing -- Examinations